2014
DOI: 10.1167/iovs.14-14201
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Shape and Gradient Refractive Index to the Spherical Aberration of Isolated Human Lenses

Abstract: Three-dimensional sOCT and LRT allowed reconstruction of lens geometry and GRIN in isolated lenses. The constancy of the GRIN axial power exponent, and the opposite slopes of surface and nucleus indices with age, explain the minor variations of the average index. Both geometrical changes and increase in the GRIN meridional power exponent contribute to the age-dependent shift of negative SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 57 publications
6
59
0
Order By: Relevance
“…Dubbelman et al showed that the asphericity of human lenses in vivo tends to increase with age for both anterior and posterior surface [22]. These results are in agreement with the report by Birkenfeld et al on ex vivo lenses [9].…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…Dubbelman et al showed that the asphericity of human lenses in vivo tends to increase with age for both anterior and posterior surface [22]. These results are in agreement with the report by Birkenfeld et al on ex vivo lenses [9].…”
Section: Introductionsupporting
confidence: 85%
“…Methods for securing human tissue were in compliance with the Declaration of Helsinki. The handling and experimental procedures, described in detail in a prior publication [9], have been approved by the institutional Review Boards of BST and Consejo Superior de Investigaciones Científicas (CSIC). The post-mortem time varied between 1 and 3 days at the time of the experiment.…”
Section: Lens Specimens and Preparationmentioning
confidence: 99%
See 3 more Smart Citations